2014
DOI: 10.1111/sms.12391
|View full text |Cite
|
Sign up to set email alerts
|

Effects of psychological priming, video, and music on anaerobic exercise performance

Abstract: Peak performance videos accompanied by music can help athletes to optimize their pre-competition mindset and are often used. Priming techniques can be incorporated into such videos to influence athletes' motivational state. There has been limited empirical work investigating the combined effects of such stimuli on anaerobic performance. The present study examined the psychological and psychophysiological effects of video, music, and priming when used as a pre-performance intervention for an anaerobic endurance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
45
1
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(51 citation statements)
references
References 40 publications
4
45
1
1
Order By: Relevance
“…The discrepancy in findings might be attributed to differing exercise modalities (cycle ergometry vs. circuit-type exercises to exhaustion), as well as the manner in which the music was used (asynchronous vs. synchronous application). Both of these are task-related situational factors that were theorized to moderate affective responses to music in a recent model (Karageorghis, 2015). For perceived activation, there was a significant (p = .020) gender x time interaction wherein FAS scores significantly increased during and decreased post-exercise for men only.…”
Section: Affective Variablesmentioning
confidence: 91%
See 1 more Smart Citation
“…The discrepancy in findings might be attributed to differing exercise modalities (cycle ergometry vs. circuit-type exercises to exhaustion), as well as the manner in which the music was used (asynchronous vs. synchronous application). Both of these are task-related situational factors that were theorized to moderate affective responses to music in a recent model (Karageorghis, 2015). For perceived activation, there was a significant (p = .020) gender x time interaction wherein FAS scores significantly increased during and decreased post-exercise for men only.…”
Section: Affective Variablesmentioning
confidence: 91%
“…This is in accordance with the average post-exercise state that is characterized by a gradual decrease in perceived activation (Ekkekakis, 2003). It also points to a specialist role that music might play in expediting post-exercise recovery through the principle of entrainment, wherein the main pulses of the body such as respiration and heart rate can be "guided" towards resting levels by appropriate musical stimuli (see Karageorghis, 2015).…”
Section: Affective Variablesmentioning
confidence: 99%
“…Although traditional views on optimizing task performance emphasize concentration on the task, studies have found that by inducing humor individuals experience more stable positive affect [32]. Priming has been applied with investigating the development of first impressions following visual primes [24], the stimulation of intrinsic motivation [33], as well as goal-directed [34,35] and competitive behavior [36].…”
Section: Introductionmentioning
confidence: 99%
“…Priming techniques may be applied to subconsciously modify the psychological state of an individual before and during a task [33]. Additionally, the use of video priming techniques to influence motivational state and anaerobic performance has also been explored with some success [35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation